SHIFTING THE LEGAL BORDERLANDS OF RULE OF LAW PROGRAMS - BRAZILIAN COOPERATION AGENCY (ABC) AND PUBLIC DEFENDERS’ OFFICE IN EAST TIMOR - Shaila, Sapna Reheem (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2019)
n this paper the author argues that the traditional international legal assistance (coined ‘rule of law’ assistance) follows a global template- sourced on the legal orders of countries that constitute the Global North. Under the rule of law (RoL) programs - legal procedures and institutions that are same as the donor nations are transferred to the recipient nations. This is because formal laws and institutions are seen as fundamental for economic prosperity and stability, and ‘copy-pasted’ as solutions separated from contexts. But in recent years with the emergence of non-traditional donors under the ‘South- South’ cooperation, following an approach of ‘mutual cooperation’ has challenged the traditional mode of international assistance on the RoL. These countries accommodate the existence of legal pluralism, as well as adopt a slower and prolonged approach by building networks with local stakeholders drawing on their post-colonial and development trajectories. Using the case study of Brazilian legal assistance through the ABC in East Timor within the Public Defenders’ Office, the author shows how non-traditional international donors has subverted the traditional model of ‘rule of law’ assistance. This paper bridges the gap between the scholarship on the South - South cooperation within development studies and the legal scholarship on law and development focusing on the rule of law reforms. Using empirical data, the paper demonstrates the distinctive approaches undertaken by the Brazilian international actors within East Timor by underlining how dominant rule of law reforms push crucial local interests to the borders/peripheries. Further, this paper poses questions on the universality of the rule of law reforms advocated by traditional donors by demonstrating the emergence of peripheral interests from the engagement of donors from the Global South